2017
DOI: 10.1080/07370016.2017.1260983
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Support Needs of Patients with Chronic Diseases in a South African Township: A Qualitative Study

Abstract: Despite the need for chronic disease self-management strategies in developing countries, few studies have aimed to contextually adapt programs; yet culture has a direct impact on the way people view themselves and their environment. This study aimed to explore the knowledge, attitudes, and self-management needs and practices of patients with chronic diseases. Four patient focus groups (n = 32), 2 patient interviews, group observations, and key informant interviews (n = 12) were conducted. Five themes emerged: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Concerns with the pharmacological management of patients with T2DM include adherence to medicines, which is typically substandard, as well as insulin resistance. A number of studies have shown the importance of healthcare professionals such as pharmacists, nurse practitioners, and community health workers, improving subsequent adherence and outcomes (Dube et al, 2017;Ong et al, 2018), with more studies planned given current concerns. We envisage that innovative approaches such as the increasing use of mobile technologies will be adopted to enhance adherence to lifestyle changes and medicines, and we will be monitoring this development in the future (Opoku et al, 2019;Owolabi and Goon, 2019).…”
Section: A) Short Termmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns with the pharmacological management of patients with T2DM include adherence to medicines, which is typically substandard, as well as insulin resistance. A number of studies have shown the importance of healthcare professionals such as pharmacists, nurse practitioners, and community health workers, improving subsequent adherence and outcomes (Dube et al, 2017;Ong et al, 2018), with more studies planned given current concerns. We envisage that innovative approaches such as the increasing use of mobile technologies will be adopted to enhance adherence to lifestyle changes and medicines, and we will be monitoring this development in the future (Opoku et al, 2019;Owolabi and Goon, 2019).…”
Section: A) Short Termmentioning
confidence: 99%
“…These include access to care in the first place, which is typically among public sector PHC facilities across most of SSA (Atun et al, 2017). Access to physicians and medicines continues to be a challenge especially if this involves high patient co-payments and/ or there are long distances and queues to see a healthcare professional, both of which have economic and emotional consequences for patients (Mendenhall and Norris, 2015;Dube et al, 2017;Nashilongo et al, 2017). The prohibitive costs of medicines in some LMICs, which can account for up to 60% or more of total healthcare costs, does affect continued medicine use including adherence for long terms conditions such as T2DM if much of this is out-of-pocket (Cameron et al, 2009;Mhlanga and Suleman, 2014;Ong et al, 2018).…”
mentioning
confidence: 99%
“…This is possibly amplified by the lack of time the doctor/nurse has with the patient due to the high patient load in the PHC facilities in South Africa, which in turn reveals the failure of the system and does not necessarily speak to the incompetence of individual health care practitioners (Selman et al, 2009;Bateman, 2012;Cobbing et al, 2014;Major-Helsloot et al, 2014). In addition, Dube et al (2017) found that nursing staff in a South African township lacked the educational material they desired and had no structured plan for self-management education on non-communicable diseases. This leads to conflicting and disorganised information shared with the patients, creating misconceptions and confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that patients living with diabetes may have a limited understanding both of the effects of the disease on the body, and of how these can be alleviated through medical management and lifestyle changes (Burkett, 2012;Diab, 2017). Moreover, most patients find the change in lifestyle required for successful treatment extremely challenging, and support from both the clinic and community is often lacking (Dube, Rendall-Mkosi, Van den Broucke, Bergh, & Mafutha, 2017;Murphy, Chuma, Mathews, Steyn, & Levitt, 2015;Zeh, Sandhu, Cannaby, & Sturt, 2012).…”
Section: Backg Rou N Dmentioning
confidence: 99%